Pemberdayaan Lansia untuk Mencegah Kolesterol dan Hipertensi dengan Optimalisasi Teh Sahdu (Saffron, Telang Biru, dan Madu) - Astuti, Yuli -; Artini, Dyah; Mumpuni, Nurpuji (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2024)
Donor recruitment services are the components of blood services. This donor recruitment activity aims to obtain voluntary blood donors and sustainable blood donors who are healthy and safe. Age is an indicator of the determination to recruit donors. The elderly are the age group that is still the target for recruiting sustainable blood donors. It can be said that donations from elderly donors also contribute to the safety and availability of blood products. These elderly donors come from new blood donors or repeat blood donors. Elderly people who will donate blood are guaranteed to be healthy and have no health problems.Elderly people are prone to experiencing high blood pressure and cholesterol levels that are above normal. This can be prevented with preventive measures, one of which is providing alternative drinks that can be used to control cholesterol and blood pressure in the elderly.This Community Service aims to screen health and empower cadres to optimize the use of sahdu tea.The results of this Community Service are health checks for the elderly with results based on blood pressure levels, the largest percentage is stage 2 hypertension (37.84%) and cholesterol levels, the largest percentage experiences hypercholesterolemia (64.86%). The socialization and simulation of making sahdu tea was attended by 37 elderly and enthusiastic respondents. Sahdu tea is distributed for 3 weeks and monitored by cadres for routine consumption